Correlation between Medication Adherence to Clinical Outcome of Patients with Type 2 Diabetes Mellitus at Permata Hati Clinic, Sukoharjo - Dhuhania, Dinda Nur; Karminingtyas, Sikni Retno (Universitas Muhammadiyah Lamongan, 2023)
Background: Diabetes mellitus is a disease characterized by increased blood glycemic levels which can cause blindness, heart disease and kidney failure. One of the factors that contribute to the failure to control blood glycemic levels in patients with diabetes mellitus is patient non-adherence in treatment.Objectives: This study aims to analyze the relationship between medication adherence and clinical outcomes of type 2 diabetes mellitus patients at the Permata Hati Clinic in SukoharjoDesign: This research is a correlation descriptive study with a cross sectional approach. The research sample was prolanis patients and suffering from type 2 diabetes mellitus who were more than 26 years old, namely 38 patients. The sampling technique uses total sampling. Compliance with patient treatment was assessed using the MMAS-8 questionnaire. The patient's clinical outcome was assessed by achieving fasting blood sugar levels. The data were analyzed using the Spearman rank test with a 95% confidence level (a = 0.05).Results: The level of adherence to taking medication for diabetes mellitus patients was at a moderate level of adherence in 17 patients (44.74%). Analysis with the Spearman rank test obtained a significance value of 0.000 with a correlation coefficient value of -0.801. This shows that there is a significant relationship between medication adherence in diabetes mellitus patients with fasting blood sugar levels.Conclusions: There is a relationship between medication adherence and clinical outcomes of diabetes mellitus patients at the Permata Hati Primary Clinic, Sukoharjo Regency